Analisis Penegakan Hukum Terhadap Aksi Pelecehan Seksual Non Fisik di Indonesia - Ani Purwati; Rahmiati; Rahmad Sujud Hidayat3; Martinus Tanga Lero (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
Sexual harassment is explained as an act that leads to a sexual desire, sexual requests, words or other sexually suggestive gestures, which make people feel happy, humiliated and embarrassed, where such reactions are normal in such circumstances, and acts it interferes with work, even the requirements for applying for work are unethical. There are physical and non-physical types of sexual harassment. There are currently legal regulations in Indonesia regarding physical sexual arrangements, while non-physical regulations do not yet have regulations that regulate them. Actually, the legal umbrella for attracting non-physical sex has been accommodated in the PKS Bill, so far, the bill has not been ratified, so it cannot be enforced. The purpose of this paper is to see how law enforcement against non-physical sexual harassment acts in Indonesia. The method of normative juridical writing with a conceptual approach. From this research, it was found that Indonesia needs to criminalize sexual/intimate harassment, both physical/physical and non-physical/non-physical orientation so that there is a legal umbrella that clearly regulates this action. This is actually already a rule in the PKS (Elimination of Sexual Violence) Bill. However, until now the bill has not been ratified, so it cannot be applied in the legal practice of our country.